From research to practice: results of 7300 mortality retrospective case record reviews in four acute hospitals in the North-East of England. Issue 2 (24th September 2017) - Roberts, Anthony Paul; Morrow, Gerry; Walkley, Michael; Flavell, Linda; Phillips, Terry; Sykes, Eliot; Kirkpatrick, Graeme; Monkhouse, Diane; Laws, David; Gray, Christopher
Abstract : Introduction: Monitoring hospital mortality using retrospective case record review (RCRR) is being adopted throughout the National Health Service (NHS) in England with publication of estimates of avoidable mortality beginning in 2017. We describe our experience of reviewing the care records of inpatients who died following admission to hospital in four acute hospital NHS Foundation Trusts in the North-East of England. Methods: RCRR of 7370 patients who died between January 2012 and December 2015. Cases were reviewed by consultant reviewers with support from other disciplines and graded in terms of quality of care and preventability of deaths. Results were compared with the estimates published in the Preventable Incidents, Survival and Mortality (PRISM) studies, which established the original method. Results: 34 patients (0.5%, 95% CI 0.3% to 0.6%) were judged to have a greater than 50% probability of death being preventable. 1680 patients (22.3%, 95% CI 22.4% to 23.3%) were judged to have room for improvement in clinical, organisational (or both) aspects of care or less than satisfactory care. Conclusions: Reviews using clinicians within trusts produce lower estimates of preventable deaths than published results using external clinicians. More research is needed to understand the reasons for this, but as the requirement for NHS Trusts to publish estimates of preventable mortality is based on reviews by consultants working for those trusts, lower estimates of preventable mortality can be expected. Room for improvement in the quality of care is more common than preventability of death and so mortality reviews contribute to improvement activity although the outcome of care cannot be changed. RCRR conducted internally is a feasible mechanism for delivering quantitative analysis and in the future can provide qualitative insights relating to inhospital deaths.